PENJAMINAN SIMPANAN/INVESTASI NASABAH BA - Atsani, Ulya (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2010)
Discussions upon the use of LPS by Sharia banks are interesting due to the existence of LPS which is believed to be identical to conventional finance system. Sharia banks have their own particular characteristics that make them different from that of conventional ones. Sharia baks operate based on the general rules of banking system and on Islamic faith and morals as well. However, laws on LPS points out that warranty functions are also applicable to sharia banks. LPS is needed to keep the public trust toward banking industries and to promote national economic stability. National economic stability is important. However, being committed to sharia laws is the most important.